(untitled) (Research, Society and Development, 2022)
Objective: To verify the profile of adults with cerebral palsy (CP) included in the studies and the parameters most utilized in the isokinetic evaluation of the muscles that move the knee. Method: Bibliografh rsearches were carried out in the databases: PubMed, LILACS, Cochrane Central Register of Controlled Trials (CENTRAL), Physiotherapy Evidence Database (PEDro) e SciELO, articles published from the beginning of each database until November 2021 were searched. The search terms used were “cerebral palsy”; "adult"; “isokinetic” or “isokinetic”; “dynamometer” or “dynamometry”; “joelho”, in Portuguese and English. Results: A total of 69 articles were found in the initial search (PubMed= 34, LILACS=12, Cochrane CENTRAL= 8, PEDro= 9 and SciELO= 6. After removing the duplicates, 46 studies remained. In the first screening by title and abstract 11 studies were selected. After reading these 11 articles in full and applying the eligibility criteria, a total of seven articles remained. Conclusion: Most studies included people of both sexes, followed by men, with bilateral CP or spastic diplegia and unilateral CP or hemiparesis. Most studies included soccer athletes with CP and did not include control group. Most used the Cybex 6000 isokinetic dynamometer, evaluated the knee extensor and flexor muscles, used the concentric contraction type and 60o/s angular velocity. Peak torque was the most studied variable and the position of the individuals, the alignment of the dynamometer axis and the lever arm were described in most studies.